2017
DOI: 10.1055/s-0037-1603503
|View full text |Cite
|
Sign up to set email alerts
|

Lower Limb Deformity Analysis and the Planning of an Osteotomy

Abstract: This review article provides an overview of lower limb deformity analysis. A brief history and radiographic standards are presented. Deformity analysis is considered in the frontal, sagittal, and axial planes, from simple to more complex cases. The authors recommended analysis methods based on their own experience of deformity correction, while acknowledging that there may be different ways to treat individual cases. Subsequently, methods for osteotomy planning to address the identified deformities are discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 94 publications
1
25
0
7
Order By: Relevance
“…For example, patients with hip pain due to excessive internal torsion should undergo DO on the proximal femur. 6 Other studies have suggested that the segment chosen for osteotomy should depend on coronal alignment; for example, if a femur is in valgus and has excessive internal torsion, the osteotomy should be done on the distal femur. 7 Alternatively, the choice of segment may be dependent on surgical results; for example, the higher rate of complications after DO on the proximal than on the distal tibia has suggested that DO should be done on the distal tibia.…”
mentioning
confidence: 99%
“…For example, patients with hip pain due to excessive internal torsion should undergo DO on the proximal femur. 6 Other studies have suggested that the segment chosen for osteotomy should depend on coronal alignment; for example, if a femur is in valgus and has excessive internal torsion, the osteotomy should be done on the distal femur. 7 Alternatively, the choice of segment may be dependent on surgical results; for example, the higher rate of complications after DO on the proximal than on the distal tibia has suggested that DO should be done on the distal tibia.…”
mentioning
confidence: 99%
“…Hem ön-arka (frontal) hem de lateral (sagittal) radyografilerde açılanma varsa bu biplanar deformite olup buna oblik plan deformitesi adı verilir (Şekil 31). [6][7][8][9][10] Açısal deformitelerin apeksi iki farklı planda olabilir. Frontal plan için medial ve lateral (varus, valgus), sagittal plan için anterior ve posterior (prokurvatum, rekurvatum) olmak üzere her düzlem için iki olasılık vardır.…”
Section: Oblik Plan Deformitesiunclassified
“…18,19 The technique, how to measure the torsion, was recently published by the same working group. 20 The authors recommend the method according to Waidelich et al 17 (►Fig. 4).…”
Section: Radiographsmentioning
confidence: 99%